2015
DOI: 10.1007/s10826-015-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Couple’s Relationship After the Death of a Child: A Systematic Review

Abstract: When a child dies, the parents must address the changes in their relationship as well as the way that these changes affect their individual adjustment. These two perspectives are addressed in this systematic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 45 publications
(68 reference statements)
6
46
0
Order By: Relevance
“…Because of the sensitive nature of the theme, careful attention was given to strategies for minimizing parents' distress (for a review on ethical considerations with bereaved parents' research, see Albuquerque, Pereira, & Narciso, 2016). All parents were interviewed individually at a place of their choice (which was most often their homes), and the interviews were conducted by the first author, a researcher with clinical experience in bereavement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the sensitive nature of the theme, careful attention was given to strategies for minimizing parents' distress (for a review on ethical considerations with bereaved parents' research, see Albuquerque, Pereira, & Narciso, 2016). All parents were interviewed individually at a place of their choice (which was most often their homes), and the interviews were conducted by the first author, a researcher with clinical experience in bereavement.…”
Section: Methodsmentioning
confidence: 99%
“…Grounded theory seeks to construct theory through an inductive process of data collection, in which new information is created from the data instead of testing theory-derived hypotheses (Gibbs, 2008). CGT adopts novel characteristics such as the importance given to context and the role of the researcher in the construction of the theory (reflexivity) and the existence of previous knowledge on the subject (for a review, see Albuquerque et al, 2016).…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This traumatic event can influence health-related behaviors, such as diet, smoking, or alcohol consumption [6]. It can also affect the couple dynamics between parents [2] and increase the risk of intimate partner violence [33]. Parental bereavement generally affects mothers more than fathers, perhaps as a result of gendered coping mechanisms or because mothers develop stronger emotional ties with their children [11,26,15,34].…”
Section: Life Course Effects Of Parental Bereavementmentioning
confidence: 99%
“…Traa et al (2015) also showed the importance of adequate dyadic coping efforts, such as stress communication, supportive behaviors, and positive dyadic coping, for the maintenance and improvement of relationship functioning in couples coping with cancer. Other reviews have shown that traumatic events, such as the loss of a child (Albuquerque et al, 2015), terror attacks (Gilber et al, 2011) and natural catastrophes like earthquakes (Marshall et al, 2017), can bring some couples closer while others demonstrate significant adjustment problems that are linked to conflict and may result in divorce (e.g., Badr and Acitelli, 2017). Adaptive processes mediate the effects of personal characteristics and stressful events on marital adjustment.…”
Section: Introductionmentioning
confidence: 99%